The Effect of Operational Efficiency, Technology Innovation, and Service Quality on the Competitiveness of Loading and Unloading Companies at the Port: Government Regulation as a Moderating Variable and Customer Satisfaction as a Mediation Variable - Wawan Rudi Berlianto; Usep Suhud; Hamidah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the influence of operational efficiency, technological innovation, and service quality on the competitiveness of cargo handling companies at ports, with government regulation as a moderating variable and customer satisfaction as a mediating variable. Operational efficiency enhances optimal resource utilization and cost reduction, while technological innovation accelerates logistics processes through automation and digitalization. Service quality plays a crucial role in fostering customer satisfaction, which contributes to loyalty and sustainable competitiveness. Government regulations ensure a structured operational framework, support innovation, and enhance efficiency through safety and sustainability standards. This research provides theoretical and practical insights for policymakers and managers in improving the competitiveness of the port logistics industry. Furthermore, empirical studies across various types of ports are recommended to understand the effects of these variables in different operational contexts.